Infrastructure planning and spatial planning: current relationships in the UK. Issue 1 (January 2020) - Marshall, Tim
Abstract : There have been discussions in a range of contexts of the links between spatial planning and actions on major infrastructure. Here this relationship is framed by considering the political, ideological and geographical drivers of state policies and actions in the fields of spatial planning and infrastructure. The empirical focus is a study of current large-scale spatial-planning activities in the UK over the last decade or so, largely within England. Analysis of these cases shows the importance of understanding planning and infrastructure together, given that the emerging initiatives on infrastructure and in big spatial planning are very much connected.